Analisis Redaksi Kinayah dalam Al-Qur’an Surah Thaha Ayat 110 - Alif Yasin Nur Haq; Ahmad Yasir Sipahutar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Kinayah is a pronunciation of something, while what is meant is not what is said, even if that meaning is used linguistically. Example: tall stature (because the person is tall), what is meant is not just the linguistic meaning, but more than that, such as high dignity. The Qur'an was revealed in very clear Arabic and literature with very beautiful wording and was easily understood by all audiences, in fact it could beat the language of the poets of that century. Al-Qur'an al-Karim is the greatest Islamic miracle in the following centuries. The language style of the Qur'an is full of essence (original meaning), majaz (non-original meaning), isti'arah (borrowing one word for another word) and kinayah (specific allusion). During the period of ignorance, the Arabs already had a very high style of literary language because they were always trained in arguing, praising and flattering and demeaning someone using language as a medium. This can be seen from the many al-mu'allaqat hanging from the Kaaba as a tribute to poets who were instrumental in producing beautiful literary works in their poetry. On the other hand, Arabic literature at its peak had no value when compared with the Koran, so that the literary language that was famous at that time, such as mua'laqatt, felt bland when compared with the language of the Koran. He can even beat the literary language of his time until now. This is because the advantage of the language of the Koran is that it has a very selective language style in choosing appropriate, beautiful, easy and harmonious vocabulary, so that it can touch the mind and heart so that many people are interested in learning and understanding it. On the other hand, the Koran is a guide to human life because it provides clear instructions for carrying out every daily activity. The Koran includes all the rules that humans need to interact with each other, as well as the rules with the natural environment and especially the rules with the Creator. In a not too long period of time, the beauty of the language of the Koran spread throughout social life. This was acknowledged by famous Arab poets at that time, as explained in the history of Ibn Abbas, that Walid bin Mughirah came to the Prophet and the Prophet read the Koran to him. So Walid's heart softened because of it.